2014
DOI: 10.1186/1472-6831-14-42
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal conditions, low birth weight and preterm birth among postpartum mothers in two tertiary health facilities in Uganda

Abstract: BackgroundLiterature reports have indicated an increase in research evidence suggesting association between periodontal disease and the risk of pre-term birth (PTB) and low birth weight (LBW). Periodontal diseases in Uganda have been documented as a public health problem, but their association to adverse pregnancy outcomes is unknown. This study was conducted to assess the association between periodontital diseases in postpartum mothers and PTB and LBW of babies in Mulago and Mbarara referral hospitals.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 25 publications
1
24
0
2
Order By: Relevance
“…This lack of an association was in agreement with Bansal and colleagues who stated that providing periodontal treatment during pregnancy may be too late to reduce the local and systemic in ammations and may be ineffective in preventing the preterm birth 22 . The other negative study ndings from the case control study in Uganda conducted by Muwazi and colleagues, was possibly limited by the use of only one group of women for a short period of time 23 . The other 13 studies retrieved did nd an association between periodontal disease and preterm birth and/or low birth weight.…”
Section: Discussionmentioning
confidence: 95%
“…This lack of an association was in agreement with Bansal and colleagues who stated that providing periodontal treatment during pregnancy may be too late to reduce the local and systemic in ammations and may be ineffective in preventing the preterm birth 22 . The other negative study ndings from the case control study in Uganda conducted by Muwazi and colleagues, was possibly limited by the use of only one group of women for a short period of time 23 . The other 13 studies retrieved did nd an association between periodontal disease and preterm birth and/or low birth weight.…”
Section: Discussionmentioning
confidence: 95%
“…Also in Africa, some studies have been done on preterm birth and low birth weight deliveries and these were signi cantly associated with poor periodontal status; for example a study done in Nigeria by Umoh and colleagues revealed that periodontal treatment was effective in preventing low birth weight deliveries 20 . In Uganda, Wandera and colleagues also found that mothers with periodontal problems and poor oral hygiene during pregnancy had a greater risk of preterm birth as opposed to mothers who did not have periodontitis during pregnancy 44 and Muwazi in Uganda in his cross-sectional study revealed the association between gingival recession and preterm birth 31 .…”
Section: Discussionmentioning
confidence: 98%
“…In this study, most of the mothers were young whereby the mean age was 27.35 (SD 5.2) ranging from 18 to 35 years and may be the reason why there was no statistical association between maternal age and preterm birth in this study. Similarly, the study done in Uganda by Muwazi who also worked on a young population which led to low prevalence of periodontitis and later led to reduced statistical power and therefore no association was found 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Periodontal disease is a chronic inflammatory disease of the soft and hard tissues that support the teeth, caused by bacterial plaque and influenced by host response factors (Zi et al, 2013;Takeuchi et al, 2013;Muwazi et al, 2013). There are two main types of conditions; gingivitis and periodontitis.…”
Section: Periodontal Disease As a Potential Risk Factor For Adverse Pmentioning
confidence: 99%
“…Some of the important clinical features include erythema of the gingiva, edema, hyperplasia, increased bleeding, alterations in the gingival color, tooth mobility, dental migration, pocket depth (Muwazi et al, 2013;Michalowicz et al, 2008). (Michalowicz et al, 2008).…”
Section: Periodontal Disease As a Potential Risk Factor For Adverse Pmentioning
confidence: 99%